Remote assessment of DMFT and number of implants with intraoral digital photography in an elderly patient population: a comparative study - Ciardo, Antonio; Sonnenschein, Sarah K.; Simon, Marlinde M.; Rütters, Maurice; Spindler, Marcia; Ziegler, Philipp; Spies, Ingvi; Spies, Alexander-Nicolaus; Kykal, Jana; Baumann, Eva-Marie; Fackler, Susanne; Büsch, Christopher; et al. (PLOS ONE, 2022)
Objectives This comparative study aimed to evaluate intraoral digital photography (IODP) as assessment-tool for DMFT and number of implants (IMPL) compared to clinical diagnosis (CLIN) in an elderly population with high restorative status. Secondary research questions were whether an additional evaluation of panoramic radiographs (PAN-X) or raters’ clinical experience influence the agreement. Methods Fifty patients (70.98±7.60 years) were enrolled for standardized CLIN and IODP. The clinical reference examiner and ten blinded raters evaluated the photographs without and with a PAN-X regarding DMFT and IMPL. CLIN were used as reference standard and differences to IODP and IODP-PAN-X findings were analysed descriptively. To assess intra-rater agreement, pairwise Gwet’s AC1s of the three diagnostic methods CLIN, IODP and IODP+PAN-X were calculated. Results Compared to a DMFT of 22.10±3.75 (CLIN), blinded raters evaluated a DMFT of 21.54±3.40 (IODP) and 22.12±3.45 (IODP+PAN-X). Mean values for “Decayed” were 0.18±0.52 (CLIN), 0.45±0.46 (IODP) and 0.48±0.47 (IODP-PAN-X), while 11.02±5.97 (CLIN), 10.66±5.78 (IODP) and 10.93±5.91 (IODP+PAN-X) were determined for “Missing” and 10.90±5.61 (CLIN), 10.43±4.85 (IODP) and 10.71±5.11 (IODP+PAN-X) for “Filled”. IMPL were 0.78±2.04 (CLIN), 0.58±1.43 (IODP), 0.78±2.04 (IODP+PAN-X). Gwet’s AC1 using the mode of the blinded raters’ assessment of "Decayed", "Missing" and IMPL compared to CLIN ranged from 0.81 to 0.89 (IODP) and 0.87 to 1.00 (IODP+PAN-X), while for "Filled" and DMFT they were 0.29 and 0.36 (IODP) as well as 0.33 and 0.36 (IODP+PAN-X), respectively. Clinical experience did not influence the agreement. Conclusions Assessment of “Decayed”, “Missing” and IMPL by IODP showed almost perfect agreement, whereas of “Filled” and DMFT revealed fair to moderate agreement with clinical findings. Additional PAN-X-evaluation increased agreement compared to IODP-diagnostics alone. IODP for the assessment of DMFT and IMPL might be a suitable method in large-scale epidemiological studies, considering high agreement in total values and miscellaneous agreement at patient-level.
Gesehen am 05.07.2022